2002
DOI: 10.2170/jjphysiol.52.129
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Signaling Mechanisms Underlying Pharmacological Action of Bak Foong Pills on Gastrointestinal Secretion.

Abstract: Bak Foong Pills (BFP, also known as Bai Feng Wan)is an over-the-counter traditional Chinese medicine (China registration No. Z980035) that has long been used for treating gynecological disorders and improving of overall body functions, including gastrointestinal (GI) function [1]. However, the cellular signaling mechanism underlying BFP action, especially on the GI tract, has not been elucidated.Secretagogue-induced Cl Ϫ secretion by the GI tract is important because Cl Ϫ secretion provides an essential drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Clinical indications also suggest that BFP has beneficial effect on overall body functional systems including the cardiovascular, digestive system as well as the reproductive system. Our previous studies has demonstrated estrogenic effect of BFP and it beneficial effect on gastrointestinal secretion, 7,8) as well as preventing/delaying development of hypertension in spontaneous hypertension rats (Zhou et al unpublished data). In order to evaluate the effect of BFP on the cardiovascular system, we undertook the present study to investigate its effect on blood coagulation and the BFP-E-ext (76 g).…”
mentioning
confidence: 93%
“…Clinical indications also suggest that BFP has beneficial effect on overall body functional systems including the cardiovascular, digestive system as well as the reproductive system. Our previous studies has demonstrated estrogenic effect of BFP and it beneficial effect on gastrointestinal secretion, 7,8) as well as preventing/delaying development of hypertension in spontaneous hypertension rats (Zhou et al unpublished data). In order to evaluate the effect of BFP on the cardiovascular system, we undertook the present study to investigate its effect on blood coagulation and the BFP-E-ext (76 g).…”
mentioning
confidence: 93%
“…Rats aged 18 months have been demonstrated to be suitable model for postmenopausal-like and old age animals. 21,22) Animals were supplied by the Laboratory Animal Service Centre of the Chinese University of Hong Kong. Animals were maintained in an air-conditioned room with controlled temperature of 24Ϯ2°C and humidity of 55Ϯ15%, in a 12 h light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…BFP has long been used as a remedy to treat gynaecological disorders, such as dysmenorrhoea, irregular menstrual cycle and irregular bleeding. Clinical indications have suggested that BFP has beneficial effects on overall body function and our previous studies have demonstrated effects of BFP, most of which to various extents are estrogen-related, on improving blood circulation, 20) gastrointestinal secretion 21) and reduce the chance of cardiovascular hypertension. 22) Menoease Pills (MBFP), is a new commercially available BFP-derived formula, with major ingredients including:…”
mentioning
confidence: 94%
“…TMP has been proposed to act as an inhibitor of phosphodiesterase (PDE) and thereby it increases intracellular cAMP [15] . We have recently demonstrated a stimulatory effect of a TMP-containing herbal formula on the anion secretion in human colonic [17] and pancreatic duct cell lines [18] , indicating the involvement of cAMP and activation of CFTR. The present study aimed to compare the stimulatory effects of TMP on colonic anion secretion in different colonic cell types, T84 and Caco-2, as well as freshly isolated rat colonic mucosa, in an attempt to assess the different contribution of these two cell types to colonic anion secretion.…”
Section: Introductionmentioning
confidence: 97%